Does Cesarean Section Increase the Risk of Postpartum Depression? A Systematic Literature Review - Alrika Febi Yuarsyah; Budi Utomo; Izzati Dwi (Universitas Andalas, 2021)
Background: Postpartum depression (PPD) is a psychological disorder experienced by mothers at 4 weeks to 6 months postpartum. One of the risk factors for postpartum depression is the type of delivery. The mode of delivery in its effect on postpartum depression has been studied extensively with conflicting results whether vaginal delivery or cesarean section (CS) that can affect postpartum depression (Rauh et al., 2012). Methods: This is a systematic literature review with a research question using PICO standard namely